Erythema. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
(...) In this chapter we will only treat the skin diseases in which erythema is the only or prominent sign. On the other hand, we will not treat the very numerous skin diseases in which erythema is associated with other skin lesions such as exudative lesions (vesicles and blisters), hyperkeratosis, scaling etc., even though the word "erythema" is included in the name of the disease (erythema nodosum, erythema multiforme, etc.). (...).